Analisis Pengaruh Strategi Pemasaran Syariah terhadap Loyalitas Konsumen pada Home Industri Tahu Andika Kecamatan Muara Tembesi Kabupaten Batang Hari - Nadiatul Khoiroh; Ridho Tri Ananda (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2022)
Strategy on Consumer Loyalty at Home Industry Tofu Andika, Muara Tembesi District, Batang Hari Regency can be concluded from the three analyzes used, from the results of multiple linear regression if Product (X1), Price (X2), Place (X3) and Promotion (X4) = 0, then Consumer Loyalty (Y) is 10,856. If Product (X1) increases by one unit, then Consumer Loyalty increases by 0.435 assuming the variables Price (X2), Place (X3), Promotion (X4) = 0 or constant , If the price (X2) increases by one unit then consumer loyalty increases by 0.350 assuming the variables Product (X1), Place (X3) and Promotion (X4) = 0 or constant, If Place (X3) increases by one unit then consumer loyalty increases by 0.513 assuming the variables Product (X1), Price (X2) and Promotion (X4) = 0 or constant and If Promotion (X4) increases by one unit then consumer Loyalty increases by 0.213 assuming the variables Product (X1), Price (X2) and Place (X3) = 0 or constant From the summary table, the value of the Marketing strategy is a mindset that will be used for a strategy carried out to achieve profitable marketing for the company, also regarding specific strategies in target market segments, positioning, as well as marketing and how much to spend on marketing. The purpose of marketing itself as a tool for marketing that already exists in the various elements of a marketing program that has been needed is also considered so that the objectives of the marketing strategy and positioning that are applied can run successfully. Marketing planning usually occurs and is arranged based on the 4Ps which become indicators, namely: product (product), price (price), place (place), promotion (promotion). This study aims to determine the condition of sharia marketing strategy and consumer loyalty as well as respondents' responses to the influence of sharia marketing strategy on consumer loyalty in the Home industry of Tofu Andika, Muara Tembesi District, Batang Hari Regency. This research is qualitative and quantitative. The sample in this study amounted to 99. The data were analyzed using 2 (two) ways, namely by using multiple linear regression and using the SPSS program to determine the factors that influence purchasing decisions with the t test and F test using the coefficient of determination simultaneously. Analysis of the Effect of Sharia Marketing coefficient of determination (r2) obtained is 0.586, which means that the influence of sharia marketing strategy on Consumer Loyalty in the Andika Tofu Home Industry is 58.6% while the remaining 42.4% is due to other factors not included in this study